Zoom-Based Arabic Learning During and Post Covid-19 - Batmang, Batmang; B, Amir; Azis, Abdul; Elhastri, Hardina; Boulahnane, Saad (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
Arabic students of IAIN Kendari are unique in terms of their living environment which still had internet network issues lead to different experiences in using Zoom. Research on the sustainability of Zoom-based Arabic learning during the Covid-19 pandemic aimed to analyze creative and innovative learning models and observe through the perception of Arabic students of IAIN Kendari towards the use of Zoom as a learning medium during COVID-19. A qualitative and phenomenological approaches were used. The data were collected by interviews and documentation. The respondents in this study were 20 Arabic course students from the 2019 batch who attended lectures using Zoom. Data analysis, data reduction, data display and conclusion were discussed. The results showed varied responses from students to Arabic learning based on Zoom. Most of the students stated that Zoom was well applied in learning compared to other media. It was also proved efficacious with a few palpable advantages, such as students’ visibility during classes and room capacity to accommodate larger numbers of students. The results illustrated that Arabic learning on Zoom, both during and post Covid-19, may continue by considering the condition of the student learning environment. After participating in distance learning through its application, the changes occurring at the level of students pertain to increased levels of involvement in the use of ICT, leading to the learners who initially did not use the platforms and switching to Zoom as a learning medium and benefiting from discussions and other existing features.